Eksploitasi Tubuh Perempuan Dalam Perfilman Horor Indonesia Studi Politik Tubuh Terhadap Film Suster Keramas - Silitonga, Natasha Abeline; Erviantono, Tedi; Puspitasari, Ni Wayan Radita Novi (Peneliti.net, 2024)
This research aims to examine how the objectification of women and the exploitation of women's bodies are depicted in the movie